2011
DOI: 10.1007/978-3-642-22321-1_20
|View full text |Cite
|
Sign up to set email alerts
|

On Prefix Normal Words

Abstract: We present a new class of binary words: the prefix normal words. They are defined by the property that for any given length k, no factor of length k has more a's than the prefix of the same length. These words arise in the context of indexing for jumbled pattern matching (a.k.a. permutation matching or Parikh vector matching), where the aim is to decide whether a string has a factor with a given multiplicity of characters, i.e., with a given Parikh vector. Using prefix normal words, we give the first non-trivi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
65
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(65 citation statements)
references
References 14 publications
(21 reference statements)
0
65
0
Order By: Relevance
“…Prefix normal words, introduced in [11] are a refinement of the abelian equivalence classes for binary alphabets {0, 1}. A word w is called prefix normal if the prefix of w of any length has at least the amount of 1s as any of w's factors of the same length.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Prefix normal words, introduced in [11] are a refinement of the abelian equivalence classes for binary alphabets {0, 1}. A word w is called prefix normal if the prefix of w of any length has at least the amount of 1s as any of w's factors of the same length.…”
Section: Introductionmentioning
confidence: 99%
“…Burcsi et al have shown in [4] that this relation is indeed an equivalence relation and moreover that each class contains exactly one uniquely determined prefix normal word -the prefix normal form. From a combinatorial point of view, prefix normal words are also of interest since they are connected to Lyndon words, in the sense that every prefix normal word is a pre-necklace [11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations